Managing educational tourism - Ritchie, Brent W. (New Delhi, India : Viva Books Private Limited, 2006)
This book outlines the main forms of educational tourism, their demand and supply characteristics, their impacts and the management issues associated with them.It argues for adequate research and appropriate management of educational forms of tourism to maximise regional development impacts and personal learning benefits.
1. An Introduction to Educational Tourism -- 2. Exploring Nature-based and Cultural Educational Tourism -- 3. Adult and Seniors' Educational Tourism -- 4. Schools' Educational Tourism / Brent W. Ritchie, Neil Carr and Chris Cooper -- 5. University and College Students' Tourism / Neil Carr -- 6. Destination Marketing, Regional Development and Educational Tourism -- 7. Conclusions and Reflections: The Future of Educational Tourism.
Includes bibliographical references and index.
Keywords: STUDENTS -- TRAVEL